Prosedur Penggunaan Sistem Pemantauan Pasar Kebutuhan Pokok (SP2KP) Berbasis Web Pada Harga Barang Kebutuhan Pokok Dan Barang Penting (BAPOKTING) Di Dinas Perindustrian Dan Perdagangan Provinsi Sumatera Barat - Miftah Huljannah. B (CV. ITTC INDONESIA, 2023)
In order to overcome the price of staple goods and important goods that continue to fluctuate, the government through the West Sumatra Provincial Office of Industry and Trade launched a web-based application, namely the Staple Needs Market Monitoring System (SP2KP). Before the existence of this application, the public did not know about the changes in the prices of staple goods and important goods that are happening at this time. So that this web-based SP2KP application was made which can make it easier for the public to see price comparisons. But, there are some people who do not understand the use of this SP2KP system. So, the writer explains the procedure for using the web-based SP2KP system in this final project.